From Oppression to Violence: The Role of Oppression, Radicalism, Identity, and Cultural Intelligence in Violent Disinhibition - Lobato, Roberto M.; Moya, Miguel; Moyano, Manuel; Trujillo, Humberto M. (Frontiers in Psychology, 2018)
Violent radicalization and terrorism continue to pose social and security problems. Starting from the theoretical framework offered by the significance quest theory, the purpose of this research was to analyze the different roles that radical intentions play in the relationship between the loss of significance and violent disinhibition in Muslims and non-Muslims. For this reason, we carried out two studies: the first one with 133 Muslims and 126 non-Muslims, and the second with 98 Muslims and 167 non-Muslims. Specifically, we measured how perceived oppression influenced violent disinhibition through radical intentions. Secondly, we also measured the impact of identity and cultural intelligence in these relations. The main finding of the research was that there was an indirect effect of perceived oppression on violent disinhibition through radical intentions in the Muslim sample, whereas, in the non-Muslim sample, the effect of perceived oppression on violent disinhibition was not mediated by radical intentions. These results were replicated in both studies. Additionally, we found that identity and culture were factors that moderated the proposed relations. This work therefore shows that the conjunction of the loss of significance and radical intentions seems to strongly exacerbate the likelihood of a process of violent disinhibition for those who are considered to be in marginal contexts. Overall, different pathways and intervening factors are in the process of radicalizing Muslims and non-Muslims in Western societies.